Improvised double-embedding technique of minute biopsies: A mega boon to histopathology laboratory - Lokendra Yadav; Sarega Thomas; Usha Kini (Wolters Kluwer Medknow Publications, 2015)
Introduction: Optimal orientation of minute mucosal biopsies is essential for a definite diagnosis in gastrointestinal pathology or to visualize neural plexuses in Hirschsprung disease. The problem of minute size of the biopsy and its orientation gets compounded when they are from neonates and mandates exhaustive strip cuts, thus delaying reporting. Aim: A modified agar-paraffin technique is aimed to make tissue embedding efficient and user-friendly by inking mapping biopsies (one or more) either fresh or fixed with surgical coloring inks followed by embedding first in agar after orientation and followed thereafter by processing, re-embedding in paraffin wax, sectioning and staining. Results: The tissues in agar paraffin block were found to be well processed, firm, held secure and well preserved. The blocks were easy to cut, with serial sections of thickness 2-3 μ and easy to spread. The colored inks remained permanently on the tissues both in the block as well as on the sections which helped in easy identification of tissues. Agar did not interfere with any stain such as Hematoxylin and Eosin or with histochemical stains, enzyme histochemistry or immunohistochemistry. Inking biopsies and pooling them in a block when obtained from the same patient reduced the number of tissue blocks. Conclusion: The modified agar-paraffin embedding technique is a simple reliable user friendly method that can greatly improve the quality of diagnostic information from minute biopsies by optimal orientation, better quality of sections, faster turnaround time and cost-effectiveness by economizing on the number of paraffin blocks, manpower, chemical reagents and laboratory infrastructure.